Polysaccharides as Potential Anti-tumor Biomacromolecules —A Review - Guo, Rui; Chen, Min; Ding, Yangyang; Yang, Pengyao; Wang, Mengjiao; Zhang, Haihui; He, Yuanqing; Ma, Haile (Frontiers in Nutrition, 2022)
Cancer, one of the most threatening diseases, has attracted worldwide attentions to develop drugs against it without side-effects. Polysaccharides belonging to bioactive macromolecules are potential to be applied in cancer therapy due to their anti-tumor activities and non-toxic characteristics. This manuscript reviewed the common prepared methods for polysaccharides, the detailed mechanisms for its anti-tumor activities, the structure-activity relationships, the absorption and metabolism of polysaccharides, and the applications of polysaccharides in anti-tumor therapy. It implied that polysaccharides with enhanced activities may be obtained by proper extraction methods. Polysaccharides consisted of β-(1→3) glycosidic bond and the triple helix structure or modified properly could exhibit prominent bioactivities especially in anti-tumor activity. Polysaccharides could be digested and absorbed in gastrointestinal tract after oral administration, which was closely associated with its anti-tumor activity. Moreover, the review pay clos attentions to the possible anti-tumor mechanisms including cell cycle arrest, anti-angiogenesis, apoptosis, immunomodulation, etc. This review could be helpful for the development of polysaccharides as new function foods and ingredients for health benefit and disease prevention.